Figures, Grounds and Containers. Patient Presentation in Medical Case Reports - Magdalena Murawska (Miscelánea: A Journal of English and American Studies, 2010)
This paper studies patient presentation in medical case reports with regard to the concept of space. It examines how the choice of specific linguistic means in the description of diagnosis and treatment can contribute to different modes of patient imaging varying in their spatial configurations. To this end, a corpus of fifty-six medical case reports has been compiled and then analysed at three stages. Firstly, accounts of the diagnosis and treatment of various patients have been investigated to determine whether the vocabulary as well as the grammatical and rhetorical structures employed exemplify general cognitive patterns. Secondly, the results have been interpreted with respect to chosen concepts from the sociology of medicine to explain certain ways of referring to the patients. Thirdly, the results have been considered in relation to the context of the production of medical case reports, as scientific discourses are shaped by the disciplines in which they are used. The analysis of the texts in question reveals that the patients tend to be textually backgrounded, while disease and medical procedures are foregrounded. As a result, there is a tendency to portray the patients in abstraction from their bodies and their mental/bodily reactions.